Óleo microencapsulado de chia e de linhaça em hambúrgueres promovendo a melhoria do perfil lipídico - Heck, Rosane Teresinha (2017)
Burgers subjected to lipid reformulation were made by replacing 50% of the fat component by microparticles containing chia (CO) and linseed (LO) oils obtained by external ionic gelation. The microparticles presented high n−3 PUFAs levels and were resistant to the pH and temperature conditions commonly used in burger processing. The lipid reformulation did not affect hardness and improved important technological properties, such as cooking loss and fat retention. In addition to reducing the fat content of burgers by up to 50%, the lipid reformulation led to healthier PUFA/SFA and n−6/n−3 ratios, and lower atherogenicity and thrombogenicity indices. The burgers with CO microparticles showed a higher lipid oxidation and a lower sensory quality compared to the other treatments. However, the substitution of pork back fat by LO microparticles did not impair the sensory quality of burgers. Therefore, the microencapsulation of n−3 PUFA-rich oils by external ionic gelation can be considered an effective strategy to produce healthier burgers.